ANALISIS METODE PEMBAYARAN PAYLATER DARI DIMENSI KEPERCAYAAN, KEAMANAN, PERILAKU BELANJA KOMPULSIF TRANSAKSI ONLINE - Diky Paramitha (Departemen Manajemen, 2022)
Abstract: A Some of the application features that support people in making transactions today in the 4.0 era include PayLater. The PayLater feature is a digital credit financial service from several digital platforms that makes it easier for users to transact online on credit. The problems faced today are mainly in terms of trust, security and compulsive shopping behavior when using the PayLater application. The purpose of this study is to analyze the PayLater payment method in terms of the level of trust, security and impulsive buying behavior in online transactions. This study uses a population of people who trade online. The sample for this research is 100 samples. This study uses a targeted sampling method using structural equation modeling partial least squares analysis (SEM-PLS). The results showed that the dimension variables of Trust and Security did not have a significant effect on the PayLater payment method, while the Compulsive Shopping Behavior dimension variable online transactions greatly influenced the PayLater payment method.